Photosynthesis of cassava (Manihot esculenta) - El-Sharkawy, Mabrouk A.; Cock, James H. (Cambridge University Press, 1990)
In recent studies of cassava at CIAT, net CO2 uptake rates of 20 to 35 ?mol CO2 m?2 s?1 were commonly observed. Cassava photosynthesis has a high optimum temperature (35°C) and a wide plateau (25 to 35°C) corresponding to the temperature range under which cassava is cultivated. Leaf photosynthesis requires high saturation irradiance (1500 ?mol m?2 s?1) and the rates are greatly reduced by leaf-air vapour pressure differences above 1.5 kPa; this reduction is associated with stomatal closure. Cassava leaves have low photorespiration, low CO2 compensation point, high percentage of carbon fixation in C4 acids and a high PEP-carboxylase activity (15 35% of that in maize), but cassava does not have the typical C4-Kranz anatomy. Field measurements of single leaf photosynthesis among a wide range of cultivars grown under rain-fed conditions showed that when light interception was not limiting, there were significant correlations between leaf photosynthesis, total biomass and root yield. This suggests that the use of parental materials with high photosynthetic capacity, in combination with other yield determinants, could be a successful strategy for developing high yielding cultivars. This might be done by exploiting any genetical variations in leaf anatomy and biochemistry that could enhance photosynthesis efficiency and hence productivity.